Stimulus Augmented Reality Children Storybook Timun Mas Membentuk Kognitif Visual Anak Usia Dini - Putri, Kinanti Erste Panggayuh; Ardiyanto, Deny Tri; Widodo, Andreas Slamet (Institut Bisnis dan Teknologi Indonesia, 2024)
The concept of visual literacy reading activities based on technology represents an implementation of the smart education paradigm, which is currently gaining recognition as a potentially transformative approach for engaging the digital native generation. The strategy of combining the power of visual-based storyteling media with virtual reality technology represents an innovation that aims to present a more engaging and enjoyable reading experience for early childhood. The objective of this study is to examine the impact of the Augmented Reality Children's Storybook (ARCS) Timun Mas media on the cognitive and visual responses of early childhood. The study employed a qualitative case study methodology with a purposive sample of children aged 4-6 years at Darrunajwa Kindergarten, Jombang, East Java. The data collection techniques selected were observation, interviews, literature studies, and documentation. The findings of the study indicate that the Timun Mas Storybook media based on Augmented Reality can facilitate the formation of five indicators of children's cognitive-visual abilities, namely visual sensory, visual attention, visual memory, visual spatial relations, and visual sequence memory. This visual response will subsequently contribute to an enhanced visual perception of children towards the forms of visual elements, storylines, and moral messages contained in the ARCS Timun Mas media.